(untitled) (American Journal of Islam and Society, 2022)
The book under review offers an analysis of Islamic theology delineated broadly under the auspices of the Ottomans and the nation-state of Turkey, in past and present. As outlined in its introduction, the book comprises five chapters: 1. Origins, 2. Nation, 3. God, 4. Humanity, 5. Futures.